Human and robotic movement in the air. (January 2020) - Hemami, Hooshang; Utkin, Vadim I.; Hemami, Mahmoud
Abstract: The long-range objective is to help the development of computational tools for all human movement on the ground and in the air. Movements that can be neurally and physiologically observed and measured contribute to unlocking the mysteries of the central nervous system (CNS). Medicine, science and engineering have successfully adopted minimal and reduced systems to understand the complexities of the human system and to offer effective solutions. The coordinate systems and the state variables the CNS utilizes are not well known. Movement in the air poses problems of dynamics, control, stability, coordination, maneuverability, landing and signal processing. Awareness of the states of the implement and how the CNS estimates these states from the available contact with it in the air is one challenge. It is assumed the head and the torso are held as one rigid body such that the angular velocities and accelerations, measured by the vestibular system, are the same as those of the torso. The vision system is not considered.